Innovation’s Effect on Brand Equity: Insights from Medical Tourists - Shriedeh, Fayez Bassam; Abd. Ghani, Noor Hasmini (Journal of Asian Business Strategy, 2016)
A market-innovative firm is presumed to have superior customer-linking values, which, in turn, is likely to lead fulfillment of superior subjective brand performance in comparison with non-innovative firms. However, empirical evidence for the argument prior knowledge is weak. Therefore, this study examines the influence of innovation capabilities on brand equity building in the medical tourism sector in Jordan. Accordingly, 384 questionnaires were systematic randomly distributed to treated medical tourists at five largest private hospitals in Amman city. Only, 306 questionnaires were used for data analysis. The findings showed that innovation contributes significantly to brand equity building. More specifically, product innovation, process innovation, and service innovation positively and significantly enhance overall brand equity. Meanwhile, administrative innovation and marketing innovation insignificantly affect overall brand equity.